Epidemiology of boxing-related upper extremity injuries in the United States - Lemme, N. J.; Ready, L.; Faria, M.; DeFroda, S. F.; Gil, J. A.; Owens, B. D. (The Physician and Sportsmedicine, 2018)
Objective: The incidence of boxing-related upper-extremity (UE) injuries in the United States has not been well characterized. Recent rule changes have been made to make participation safer for athletes, although the consequences of such rule changes on injury rates is unclear. Therefore, we sought to determine the incidence, characteristics, and trends of boxing-related UE injuries.